TINJAUAN MINAT WISATAWAN TERHADAP PENGEMBANGAN DAYA TARIK WISATA DI SAMOSIR - Sarah Betty Tiomsi Simamora (Adisam Publisher, 2025)
Development of tourist attractions in an area must consider several important things so that the special characteristics of the area are not lost. In the development process which aims to improve people's welfare, also to continue to preserve natural and human resources in the area. The Samosir area which has a long history related to the past of its people and also the process of the formation of Lake Toba millions of years ago can be used as a basis for development to advance the Samosir area by developing new areas that are still natural and combined with the charm of artificial tourism that can make natural areas get new views and nuances without having to eliminate the original values of the area. Human resource development is a determinant of this success. Human resources who have a strong character to protect and preserve nature will be able to provide various solutions related to basic problems in a tourist area. Starting from planning road and building infrastructure, arranging parking patterns and places, lodging, and signs related to prohibitions that are easy to understand and obey by visitors, reducing and eliminating the extortion mentality in tourist attractions.